Preparation method of edible tableware material

By using starch slurrying method and citric acid plasticizing crosslinker in edible tableware materials, combined with the Plulanase hydrolysis treatment layer, the imbalance between mechanical properties and water resistance of existing tableware materials is solved, and the effects of high strength, water resistance and palatability are achieved, and production costs are reduced.

CN120116387APending Publication Date: 2025-06-10CENTRAL SOUTH UNIVERSITY OF FORESTRY AND TECHNOLOGY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510312333.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-17
Publication Date
2025-06-10

AI Technical Summary

Technical Problem

The existing edible tableware materials are unbalanced between mechanical properties and water resistance, with contradictory taste and functionality, and there is a conflict between the shelf life and the addition of preservatives, making it difficult to achieve mass production through low-cost processes.

Method used

The starch slurry method is used to heat and gelatinize, and mold it on the surface of the mold. The plasticizing crosslinker citric acid is added to improve toughness. The enzyme treatment layer is hydrolyzed with plulanase or starch debranching enzyme to improve flexibility and surface smoothness.

Benefits of technology

It realizes the high strength, water resistance and palatability of tableware materials, while reducing production costs, simple process, mass production through low-cost processes, and has antibacterial properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120116387A_ABST
    Figure CN120116387A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an edible tableware material, and relates to the technical field of food and material processing. The preparation method of the edible tableware material comprises the following steps: preparing tableware with a double-layer structure by using a template method, wherein the inner layer adopts a citric acid-starch layer; and forming a pullulanase (or starch debranching enzyme) treatment layer on the basis of the inner layer, and drying to prepare the edible tableware material. The pullulanase is used for hydrolyzing the gelatinized starch, the prepared edible tableware material has good flexibility and mechanical property, low production cost and controllable degradation speed, the problem that the mechanical property and degradation efficiency of an existing degradable tableware material are difficult to consider at the same time is solved, and the edible tableware material is simple in production process, environmentally friendly and high in economic value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of food and material processing, and particularly relates to a preparation method of an edible tableware material. Background Art

[0002] Edible tableware is an environmentally friendly tableware made from natural edible raw materials, and through special processes, it has the functionality of tableware and the characteristics of being directly edible. In recent years, with the promotion of the "plastic ban" policy globally and consumers' emphasis on the concept of health and environmental protection, edible tableware has successfully replaced traditional plastic tableware as an important research direction. Compared with traditional petroleum-based plastics, edible tableware can be directly eaten or naturally degraded after use, reducing white pollution from the source and meeting the requirements of circular economy and sustainable development. Although the mainstream degradable tableware on the current market (such as polylactic acid PLA tableware) can partially alleviate environmental pollution problems, its degradation requires specific industrial composting conditions, and there are still problems such as a long degradation period and residual microplastics in the natural environment. In contrast, due to the natural raw materials and completely biodegradable characteristics of edible tableware, it shows greater application potential in fields such as food delivery, airline food, and children's tableware.

[0003] However, there are generally key technical bottlenecks in existing edible tableware materials. For example, the imbalance between mechanical properties and water resistance: taking starch-based tableware materials as an example, they are prone to softening and deformation in a humid environment; the contradiction between taste and functionality: for example, by adding sodium alginate, the strength of the tableware material can be significantly enhanced, but the finished product will have an obvious fishy smell and be sticky when chewed, seriously affecting the eating experience; the conflict between shelf life and the addition of preservatives: for example, by adding potassium sorbate, the shelf life can be extended to 6 months, but the use of chemical preservatives violates the "pure natural" product positioning.

[0004] For example, patent document CN114311721A discloses a preparation method of an edible and biodegradable tableware: under heating conditions, a gelling agent A and a cross-linking agent are made into a mixed aqueous solution, cooled to make a tableware mold, and then the prepared tableware mold is placed in an aqueous solution of gelling agent B and left standing. The gelling agent B and the cross-linking agent in the tableware mold cross-link on the surface of the mold to form a tableware blank, the tableware blank is separated from the mold, and after separation, the tableware blank is dried to obtain the finished tableware. The gel tableware prepared by this invention has the characteristics of being edible and biodegradable, and its preparation method is novel, prepared by the endogenous diffusion method, but the types of raw materials used are complex and the manufacturing process is also relatively complex.

[0005] Therefore, it is of great practical significance to develop an edible tableware material with high strength, water resistance, palatability and capable of being mass-produced through a low-cost process. Summary of the Invention

[0006] To solve the problems existing in the materials of edible tableware in the prior art, the present invention provides a preparation method of an edible tableware material. The tableware material prepared by this method has the characteristics of being edible and biodegradable, and can achieve good mechanical properties and a controllable degradation rate.

[0007] The technical solution adopted by the present invention to solve its technical problems is to provide a preparation method and application of an edible tableware material.

[0008] The first aspect of the present invention lies in providing a preparation method of an edible tableware, including the following steps:

[0009] S1. Starch sizing: Mix starch and water in a certain proportion to obtain a starch slurry; then add a plasticizing crosslinking agent and gelatinize under heating conditions to obtain a gelatinized liquid;

[0010] S2. Take an appropriate amount of the gelatinized liquid prepared in step S1 and form it on the surface of a mold to obtain the first layer;

[0011] S3. Take the gelatinized liquid prepared in step S1, add pullulanase or starch debranching enzyme for hydrolysis to obtain a hydrolyzed liquid; then take the hydrolyzed liquid and form a second layer on the surface of the first layer prepared in step S2, and the edible tableware can be obtained after drying;

[0012] Preferably, when the tableware prepared by the present invention is in use, the first layer of the tableware is in direct contact with food. Both layers of the tableware prepared by the present invention are made of food raw materials and can be in direct contact with food. Preferably, the inner layer with better water resistance is in direct contact with food.

[0013] Furthermore, the starch is selected from one or a combination of wheat starch, corn starch, potato starch, tapioca starch, pea starch, mung bean starch, sweet potato starch, japonica rice starch, barley starch, glutinous rice starch, buckwheat starch, oat starch, sorghum starch, plantain starch, taro starch. Further preferably, it is selected from one or a combination of wheat starch, corn starch, potato starch, tapioca starch, pea starch, mung bean starch, sweet potato starch, and rice starch.

[0014] In a preferred embodiment of the present invention, pea starch is used;

[0015] Furthermore, the plasticizing crosslinking agent is selected from one or a combination of citric acid, glycerol, sorbitol, maltitol, xylitol, polyethylene glycol, citrate, monoglyceride, lactate, propylene glycol, acetylated monoglyceride, tannic acid, sodium tripolyphosphate, sodium alginate, malic acid, chitosan, calcium acetate, zinc acetate, calcium gluconate, zinc gluconate, calcium lactate, sodium phytate.

[0016] In some preferred embodiments of the present invention, the plasticizing crosslinking agent is citric acid. Selecting citric acid and adding it into the tableware material can effectively improve the toughness of the starch-based tableware material, enabling the tableware to withstand a certain degree of external force without deformation / damage and extending its service life. On the other hand, adding citric acid can make the material more smooth during the processing, solving processing problems such as difficult material forming and uneven surface.

[0017] Further preferably, the purity of the citric acid is not less than 99%, and high-purity citric acid can effectively ensure its stable plasticizing, crosslinking and pH value regulating effects in the material.

[0018] Furthermore, in step S1, the dosage of the plasticizing crosslinking agent is 0.5wt%-30wt% of the starch slurry. Preferably, the dosage of the plasticizing crosslinking agent is 0.5wt%-5wt% of the starch slurry.

[0019] In some embodiments, in step S1, the gelatinization temperature is 55-95°C; the gelatinization time is 5-30 min.

[0020] In some embodiments, in the starch slurry, the ratio of starch to water is 1:7-1:10.

[0021] In a preferred embodiment, the ratio of starch to water in the starch slurry is 1:9;

[0022] In step S3, the addition amount of pullulanase or starch debranching enzyme is: based on starch, 1 mL of pullulanase or starch debranching enzyme is added per 8-12 g of starch. In some embodiments, the concentration of pullulanase or starch debranching enzyme is 30-200 U / mL.

[0023] In some preferred embodiments, based on starch, 1 ml of pullulanase (104 U / mL) is added per 10 g of starch;

[0024] Furthermore, in step S3, the hydrolysis time is 2-30 min; in a preferred embodiment, the hydrolysis time is 5 min;

[0025] Furthermore, the hydrolysis temperature is 50-65°C; in a preferred embodiment, the hydrolysis temperature is 60°C;

[0026] Furthermore, the pH range of hydrolysis is 5.5-6.5, and in a preferred embodiment, pH = 6.

[0027] Furthermore, in step S3, the formation method of the hydrolysis solution on the first layer surface includes but is not limited to casting, spraying, dip coating or brush coating.

[0028] In some preferred embodiments, the forming method is to mix and gelatinize citric acid and starch, then inject the mixture into a mold to obtain the first layer, and then hydrolyze the gelatinized starch solution with pullulanase for 5 minutes to obtain the second layer.

[0029] The second aspect of the present invention is to provide an edible tableware prepared by the above-mentioned preparation method, and the tableware includes but is not limited to lunch boxes, straws, bowls, plates, cups, spoons, and forks.

[0030] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0031] (1) The production process of the method provided by the present invention is simple, only requiring two steps, with high production efficiency, low cost, and safe process; the components for preparing the tableware are simple, and the raw and auxiliary materials are all edible materials. The prepared tableware materials are edible and harmless to both the human body and the environment.

[0032] (2) The present invention first provides a preparation method for an edible tableware material: using a template method to prepare a tableware with a double-layer structure. The inner layer adopts a citric acid-starch layer, and a dense structure is formed during the gelatinization process, which can enhance the mechanical strength and water resistance of the material. Moreover, the residual acidity of citric acid can also inhibit microorganisms and has certain antibacterial properties; the outer layer adopts an enzyme treatment layer, and enzymatic hydrolysis reduces the amylopectin degree of starch, improving flexibility and surface smoothness, and at the same time reducing food adhesion.

[0033] (3) The tableware prepared based on this method has a clean and flat appearance after drying; it has good mechanical properties, does not collapse after being soaked in pure water, has good waterproof performance, and can withstand a certain degree of external force without deformation. Description of the Drawings

[0034] The drawings are used to provide a further understanding of the present application and constitute a part of the specification. Together with the embodiments of the present application, they are used to explain the present application and do not constitute a limitation to the present application. In the drawings:

[0035] Figure 1 It is the water absorption test result of the products prepared in Example 2 and Comparative Example 1 of the present invention;

[0036] Figure 2 It is a photo of the straw sample prepared in the example of the present invention;

[0037] Figure 3 It is a photo of the immersion experiment of the straw sample prepared by adding 1wt% citric acid in Example 2 of the present invention;

[0038] Figure 4 It is the texture property - hardness of the straw sample prepared in the example of the present invention;

[0039] Figure 5 It is the texture property - elasticity of the straw sample prepared in the example of the present invention. Detailed Embodiments

[0040] To make the above objects, features, and advantages of the present invention more apparent and understandable, the following will provide a detailed description of the specific embodiments of the present invention in conjunction with the embodiments of the specification. Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can also be implemented in other ways different from those described herein. Those skilled in the art can make similar generalizations without departing from the connotation of the present invention. Therefore, the present invention is not limited by the specific embodiments disclosed below.

[0041] The determination of the water absorption rate of the edible tableware material in the embodiment refers to the master's thesis "Research on the Influence of Different Additives on the Structure and Properties of Starch-based Straws" published by Zhang Jinyu. The water absorption test results are shown in Figure 1 .

[0042] Performance Determination Method

[0043] Water absorption: First, weigh the sample and record it as W 1 . Next, soak the samples in a constant temperature water bath containing 100 mL at temperatures of 25 °C, 45 °C, and 70 °C for 30 min. After soaking, quickly remove the excess water on the surface with filter paper and weigh again, recording it as W 2 . Calculate according to the formula: Water absorption = W 2 - W 1 .

[0044] Soaking experiment: Considering the actual application of the starch-based tableware material, pure water soaking is carried out at different temperatures (4 °C, 25 °C, 45 °C, 70 °C); at the same time, soaking experiments are carried out in combination with different application scenarios (cola at 25 °C; light soy sauce at 25 °C; white vinegar at 25 °C).

[0045] Texture analyzer: The performance of the samples before and after soaking is measured by a TPA texture analyzer. The soaked samples are soaked in a constant temperature water bath at different temperatures in different scenarios for 30 min, and then the hardness and elasticity when the elastic deformation of the samples reaches 50% are measured using a P36R probe. The experimental parameters before and after soaking are the same, both being: test speed 0.5 mm / s, trigger point load 3 g.

[0046] In the embodiments and comparative examples of the present invention, pullulanase is used to treat starch, and pullulanase solution with a concentration of 104 U / mL is used. Other concentrations or forms of enzyme solutions can also be used.

[0047] Example 1

[0048] After mixing pea starch and water evenly at a ratio of 1:9, add 1 wt% citric acid of the gelatinization solution respectively, put it in a water bath at 90 °C for gelatinization for 15 min, and then pour a certain amount of starch gelatinization solution into the mold to take the first layer, that is, the inner layer.

[0049] After gelatinization, it was cooled to 60 °C and transferred to a water bath at 60 °C. 1 mL of pullulanase (based on 10 g of starch) was added and hydrolyzed for 5 min, 10 min, 15 min, and 20 min respectively. Then, a quantitative and equal amount of the starch hydrolysis solution was poured into the mold again and adhered to the first layer. The second layer, i.e., the outer layer, was taken. Subsequently, it was demolded and placed in an oven at 35 °C under slow air-blowing conditions until completely dry to obtain a tableware material sample.

[0050] Sensory evaluation was carried out on the starch-based material samples prepared with different enzymatic hydrolysis times. It was found that the materials prepared with enzymatic hydrolysis times of 5 min and 10 min had a smooth and clean appearance and no protrusions on the surface. In subsequent experiments, the enzymatic hydrolysis time was 5 min.

[0051] The straw sample prepared by hydrolyzing for 5 min is as Figure 2 shown.

[0052] Example 2

[0053] After pea starch and water were mixed evenly at a ratio of 1:9, 1 wt%, 2 wt%, 3 wt%, and 4 wt% of citric acid in the gelatinization solution were added respectively. It was placed in a water bath at 90 °C for gelatinization for 15 min. Then, a quantitative starch gelatinization solution was poured into the mold to take the first layer, i.e., the inner layer.

[0054] After gelatinization, it was cooled to 60 °C and transferred to a water bath at 60 °C. 1 mL of pullulanase solution (based on 10 g of starch) was added and hydrolyzed for 5 min. Then, a quantitative and equal amount of the starch hydrolysis solution was poured into the mold again and adhered to the first layer. The second layer, i.e., the outer layer, was taken. Subsequently, it was demolded and placed in an oven at 35 °C under slow air-blowing conditions until completely dry to obtain a tableware material sample.

[0055] As Figure 1 shown, as the temperature of the immersion water bath increased, the water absorption rate of the sample was higher. And as the addition amount of citric acid increased, the water absorption rate of the sample gradually increased. This may be because excessive citric acid caused the degradation of starch molecules during gelatinization, exposing more hydrophilic hydroxyl groups, which can bind more water molecules.

[0056] As Figure 3 shown: The immersion experiment of the straw sample prepared with 1 wt% citric acid added. The starch-based material sample treated with 1 wt% addition amount of citric acid had a slightly curved surface and was transparent in color and did not collapse after being immersed in a pure water constant temperature water bath at 25 °C, 45 °C, and 70 °C for 30 min.

[0057] The water resistance performance of the material sample treated with 2 wt% citric acid added was verified in the same way. After being immersed in a constant temperature water bath at 25 °C and 45 °C for 30 min, it was transparent in color and did not collapse; after being immersed in a constant temperature water bath at 70 °C for 30 min, it would collapse and break, but it could still maintain a certain hardness and elasticity.

[0058] Samples of starch-based materials prepared by treating with citric acid at 3 wt% and 4 wt% were verified in the same way. They had a smooth and clean appearance. After being soaked in pure water at a constant temperature in a water bath at different temperatures for 30 minutes, they were transparent in color, still maintained a certain hardness and elasticity, could keep their shape without collapsing, and had a certain waterproof ability.

[0059] Example 3

[0060] Weigh 5 wt%, 10 wt%, 15 wt% and 20 wt% of glycerol, and put them into a beaker in which pea starch and water are mixed in a ratio of 1:9 respectively. After mixing them evenly, put them into a water bath at 90 °C for gelatinization for 15 minutes. Then, pour a certain amount of starch gelatinization liquid into a mold to take the first layer, that is, the inner layer.

[0061] After gelatinization, cool it to 60 °C, transfer it to a water bath at 60 °C, add 1 mL of pullulanase and hydrolyze for 5 minutes. Then, pour a certain amount and the same amount of starch hydrolysis liquid into the mold again, adhere it to the first layer, and take the second layer, that is, the outer layer. Subsequently, demold it and put it into an oven at 35 °C and dry it to complete dryness under the condition of slow air blowing to obtain samples of tableware materials.

[0062] Sensory evaluation was carried out on the samples of starch-based materials prepared by adding glycerol. It was found that the materials prepared when the enzymolysis time was 5 minutes had a smooth and clean appearance and no protrusions on the surface. However, after the soaking experiment, it was found that the starch-based materials prepared by adding glycerol were easily decomposed and collapsed after soaking and could not maintain their original shape.

[0063] Comparative Example 1

[0064] Mix pea starch and water evenly in a ratio of 1:9 respectively, then put them into a water bath at 90 °C for gelatinization for 15 minutes. Then, pour a certain amount of starch gelatinization liquid into a mold to take the first layer, that is, the inner layer. After the surface is dried, immerse it in the starch gelatinization liquid again, adhere it to the first layer to form the second layer. After demolding, put it into an oven at 35 °C and dry it to complete dryness under the condition of slow air blowing to obtain samples of tableware materials.

[0065] Sensory evaluation and soaking experiment were carried out on the samples of materials prepared by drying pure gelatinized starch liquid in Comparative Example 1. It was found that the samples of materials prepared from pure gelatinized starch liquid had a smooth and clean appearance, but their own strength was weak and they were fragile, and they were easily collapsed after soaking for 30 minutes.

[0066] Comparative Example 2

[0067] Mix pea starch and water evenly in a ratio of 1:9 respectively, then put them into a water bath at 90 °C for gelatinization for 15 minutes. Then, pour a certain amount of starch gelatinization liquid into a mold to take the first layer, that is, the inner layer.

[0068] The gelatinized solution was cooled and transferred to a water bath at 60 °C. 1 mL of pullulanase with a concentration of 104 U / mL was added and hydrolysis was carried out for 5 min. Then, a quantitative and equal amount of starch hydrolysis solution was poured into the mold again and adhered to the first layer. The second layer, i.e., the outer layer, was taken. Subsequently, it was demolded and placed in an oven at 35 °C and dried to complete dryness under slow air blowing conditions to obtain a tableware material sample.

[0069] Through the soaking experiments of the samples prepared with an enzymatic hydrolysis time of 5 min (prepared in Comparative Example 2) in a constant temperature water bath at different temperatures and different scenarios, the samples would crack and collapse and could not maintain their original shape. Due to the poor thermal stability of starch and its easy water absorption, the mechanical properties of materials made from starch as raw materials were limited and the waterproof performance was poor.

[0070] Characterization of the mechanical properties of the samples:

[0071] As Figure 4 shown, the hardness retention rate of the samples indicated that for the samples treated with citric acid at addition amounts of 1 wt%, 2 wt% and 3 wt%, as the soaking temperature increased, the hardness retention rate of the samples decreased significantly; for the samples treated with citric acid at an addition amount of 4 wt%, the decrease in the hardness retention rate was relatively stable, and the hardness of the samples before and after soaking was similar. Even after water absorption, they could maintain a certain hardness.

[0072] As Figure 5 shown, the elastic force increase rate of the samples indicated that for the samples treated with citric acid at addition amounts of 1 wt% and 2 wt%, as the water bath temperature increased, the elastic force increase rate of the samples increased more and the increase was stable; for the samples treated with citric acid at addition amounts of 3 wt% and 4 wt%, the elastic force increase rate increased less and the increase was stable, indicating that the hardness of the samples before and after soaking was similar and the samples absorbed less water.

[0073] Exemplary description of the preparation method of the tableware: In a set of exemplary experiments of the present invention, to prepare an edible straw, a glass rod was used as a mold. The glass rod was immersed in the gelatinized solution and then taken out and dried until the surface was dry to obtain the first layer. Then, the glass rod coated with the first layer was immersed in the hydrolysis solution, and the second layer was adhered to the surface of the first layer. After demolding, it was placed in an oven at 35 °C and dried to complete dryness under slow air blowing conditions to obtain an edible straw.

[0074] In the preparation process of the tableware prepared by the preparation method of the present invention, two layers were formed in batches. When the components of the two layers were close to dry solidification, they could directly form a whole. The inner layer was denser and more water-resistant, and the outer layer was smoother; both the inner and outer layers of the tableware were made of food raw materials, could directly contact food, and were edible. In most application scenarios, the inner layer directly contacted food and was more water-resistant; the outer layer was more suitable for contacting the user and was not sticky.

[0075] In some embodiments, the layer thickness of the two-layer structure of the tableware of the present invention can be adjusted by adjusting the viscosities of the gelatinization liquid and the hydrolysis liquid. Or by increasing the corresponding number of film-forming times to increase the thickness; preferably, the thickness ratio of the first layer to the second layer is in the range of 5:1 - 1:1.

[0076] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit them. Although the present invention has been described in detail with reference to the preferred embodiments, those of ordinary skill in the art should understand that the technical solutions of the present invention can be modified or equivalently replaced without departing from the spirit and scope of the technical solutions of the present invention, and they should all be covered within the scope of the present invention.

Claims

1. A method for preparing edible tableware, characterized in that: The following steps are involved: S1. Starch slurry preparation: starch and water are mixed in proportion to obtain starch slurry; a plasticizer and cross-linking agent are then added, and gelatinization is performed under heating conditions to obtain a gelatinized liquid; S2. Take an appropriate amount of the gelatinized liquid obtained in step S1 and shape it on the surface of the mold to obtain a first layer; S3. Take the gelatinized liquid obtained in step S1, add pullulanase or starch debranching enzyme to hydrolyze it to obtain a hydrolyzate; then take the hydrolyzate to form a second layer on the surface of the first layer obtained in step S2, and after drying, edible tableware can be obtained.

2. The method for preparing edible tableware according to claim 1, characterized in that: The starch is selected from one or a combination of wheat starch, corn starch, potato starch, tapioca starch, pea starch, mung bean starch, sweet potato starch, and rice starch.

3. The method for preparing edible tableware according to claim 1, characterized in that: The plasticizer cross-linking agent is selected from one or a combination of citric acid, glycerol, sorbitol, maltitol, xylitol, polyethylene glycol, citrate, monoglyceride, lactate, propylene glycol, acetylated monoglyceride, tannic acid, sodium tripolyphosphate, malic acid, calcium acetate, zinc acetate, calcium gluconate, zinc gluconate, calcium lactate, and sodium phytate.

4. The method for preparing edible tableware according to claim 1, characterized in that: In step S1, the amount of the plasticizer cross-linking agent used is 0.5wt%-30wt% of the starch slurry.

5. The method for preparing edible tableware according to claim 4, characterized in that: The amount of the plasticizer cross-linking agent is 0.5wt%-5wt% of the starch slurry.

6. The method for preparing edible tableware according to claim 1, characterized in that: In step S1, the gelatinization temperature is 55-95°C; the gelatinization time is 5-30min; And / or, in the starch slurry, the ratio of starch to water is 1:7-1:

20.

7. The method for preparing edible tableware according to claim 1, characterized in that: In step S3, the amount of pullulanase or starch debranching enzyme added is: based on starch, 1 mL of 30-200 U / mL pullulanase or starch debranching enzyme is added for every 8-12 g of starch.

8. The method for preparing edible tableware according to claim 1, characterized in that: In step S3, the hydrolysis time is 2-30 min; and / or, the hydrolysis temperature is 50-65°C; and / or, a pH range of 5.5-6.

5.

9. The method for preparing edible tableware according to claim 1, characterized in that: In step S3, the hydrolyzate is formed on the surface of the first layer by a method including but not limited to casting, spraying, dipping or brushing.

10. Edible tableware obtained by the preparation method according to any one of claims 1 to 9, characterized in that: The tableware includes but is not limited to lunch boxes, straws, bowls, plates, cups, spoons, and forks.

Citation Information

Patent Citations

  • Preparation method of edible and biodegradable tableware

    CN114311721A